2015
DOI: 10.1038/bjc.2015.307
|View full text |Cite
|
Sign up to set email alerts
|

KRAS, NRAS, BRAF mutation comparison of endoscopic and surgically removed primary CRC paired samples: is endoscopy biopsy material adequate for molecular evaluation?

Abstract: Background:An everyday clinical practice dilemma in the 20–30% of metastatic colorectal cancer (CRC) patients that have not been operated on their primary tumour, is, under which specific histopathology and molecular circumstances, an endoscopic biopsy could be considered adequate to provide a representative RAS/BRAF molecular status to guide treatment.Methods:A consecutive series of 193 paired biopsy and primary CRC tumour samples between August 2008 and 2010 available in the Department of Pathology archives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Indeed, data of phase III TRIBUTE study showed that small samples were more likely to fail for molecular profiling with a failure rate of 55 to 65% in small samples (bronchoscopic transbronchial needle aspiration and CT-guided biopsy) compared with 24% in larger excisional biopsy or resection specimen [16]. In our study bronchoscopy showed the lowest results, according to literature [20]. The CT-guided biopsies had intermediate results with 67% of success, between surgery/palpation biopsy and endoscopic biopsies.…”
Section: Discussionsupporting
confidence: 47%
“…Indeed, data of phase III TRIBUTE study showed that small samples were more likely to fail for molecular profiling with a failure rate of 55 to 65% in small samples (bronchoscopic transbronchial needle aspiration and CT-guided biopsy) compared with 24% in larger excisional biopsy or resection specimen [16]. In our study bronchoscopy showed the lowest results, according to literature [20]. The CT-guided biopsies had intermediate results with 67% of success, between surgery/palpation biopsy and endoscopic biopsies.…”
Section: Discussionsupporting
confidence: 47%
“…Technical issues are extensively discussed in the literature [19]. There is a general agreement that biopsy samples could be a reliable alternative to primary tumours for RAS and BRAF mutational profiling [20]. Instead, regarding MSI status, poor data are available on sampling issues.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 It was proved that the patients with BRAF mutations, especially V600E mutations did not react with anti-HER2 treatment. 8 , 18 , 19 Therefore, the development of novel anti-HER2 therapeutic agents for CRC treatment is an urgent need.…”
Section: Introductionmentioning
confidence: 99%